Cognitive maps in early entrepreneurship stages: From motivation to implementation - Santos, Susana Correia (2014)
The purpose of this research is to contribute to the explanation of cognitive maps during early entrepreneurship stages. Three groups were selected to represent different developmental states in early entrepreneurship. Individual interviews were conducted, the data were computer content analysed and cognitive maps were extracted. The results show that entrepreneurship experience develops the structure of cognitive maps, increasing clarity, richness and experience-based features. The originality of the research resides in the inclusion of entrepreneurial motivation in business opportunity recognition and the decision to launch a venture model. Through a cross-sectional design, a temporal perspective is captured by including different entrepreneurship stages.